Field efficacy of bio-control agents for eco-friendly management of sheath blight disease in rice caused by Rhizoctonia solani Kuhn - K.B. PUN, S. LENKA* and (Indian Phytopathology, 2016)
The present study was undertaken to assess the per cent disease incidence and grain yield against sheath blight (Rhizoctonia solani Kuhn) of rice through treatment of six bio-control agent formulations under field condition during kharif season of 2012 and 2013. One standard fungicide validamycin 3% L (Sheathmar-3) was taken for comparision with the field efficacy of the bio-control agents taken in the experiment. During kharif, 2012, the bio-control agent Trichoderma viride (OUAT, Bhubaneswar collection)showed maximum reduction (49.5%) of sheath blight incidence and maximum grain yield of 4.86t/ha followed by treating with T. viride (Pest Control India collection) which showed 43.3% reduction in disease incidence and grain yield of 4.48t/ha. On the other hand, from the experiment conducted during kharif, 2013, the bio-control agent T. viride (PCI collection) showed maximum sheath blight reduction of 53.8% and maximum grain yield of 4.94t/ha followed by treatment of T. viride (OUAT, Bhubaneswar collection) showing 45.8% sheath blight reduction and grain yield of 4.33t/ha.